2013
DOI: 10.2298/sarh1302109r
|View full text |Cite
|
Sign up to set email alerts
|

Novelties in gout

Abstract: Chronic asymptomatic hyperuratemia (HUA), gout paroxysm in patients with chronic hyperuratemia (HU) and normouricemic attacks of gouty arthritis are well known, but poorly understood. A review of the current literature with attempt of its explanation is presented. The natural course of gout is associated with joint structure changes that may be evaluated by different imaging techniques; comparative advantages and shortcomings of each technique are presented. For almost over 50 years the market has not offered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Owing to advanced imaging techniques (ultrasound, magnetic resonance imaging, computed tomography), asymptomatic synovial sheath inflammation can be seen in joints that have never been presented with the traditional, clinically visible gout arthritis [11][12][13][14][15]. It can also be presented in the so-called intercritical period (between two apparent gout arthritis attacks).…”
Section: Ultrasonography In Gout and Asymptomatic Hyperuricemiamentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to advanced imaging techniques (ultrasound, magnetic resonance imaging, computed tomography), asymptomatic synovial sheath inflammation can be seen in joints that have never been presented with the traditional, clinically visible gout arthritis [11][12][13][14][15]. It can also be presented in the so-called intercritical period (between two apparent gout arthritis attacks).…”
Section: Ultrasonography In Gout and Asymptomatic Hyperuricemiamentioning
confidence: 99%
“…Recently discovered phenomenon of NETosis (NET -neutrophil extracellular traps) in gout has enabled a closer evaluation of AHU [7][8][9][10], together with advanced imaging techniques [11][12][13][14][15], in vivo and in vitro laboratory studies, retro and prospective cohort studies and randomized interventional trials. They have all shown that UA is not only a marker, but also a mediator of hypertension and renal dysfunction, thus offering arguments for the present diagnostic and therapeutic recommendations amendment proposal.…”
Section: Introductionmentioning
confidence: 99%